Pertumbuhan dan Perkembangan Kawasan Perkotaan di Kabupaten: Studi Kasus Kabupaten Sleman, Daerah Istimewa Yogyakarta - Wildha Badrus Subkhi; Fadjar Hari Mardiansjah (Jurnal Wilayah dan Lingkungan, 2019)
Many small urban areas experience rapid population growth that create significant challenges in providing infrastructure and urban services. Especially in Java, Indonesia, many small urban centers are formed, grown and developed in the urbanization process of many kabupaten (non-urban districts), so made them have many urban areas in their territory. Using the case of Kabupaten Sleman in Yoogyakarta, this study is aimed to analyzes and to comprehend the growth and development of urban areas in kabupaten’s territory. The research employs a quantitative method that uses statistical data gathered from podes (villages monograph) data, monograph of the kecammatan or sub-districts, and monograph of the kabupaten or non-urban districts.The analysis observes the growth of urban areas in the kabupaten during 1990 to 2010, and the growth and development of the urban areas is observed in twoaspects, namely the observation to the expansion of the urban areas by using the development of their urban villages and the growth of their population. The research reveals that Kabupaten Sleman experiences rapid urban growth in its territory, which is also characterized by urban population explosion, especially after 2000. The growth of urban areas occurs in both internally as well as the expansion of the urban areas into surrounding (externally), which is also influenced by the expansion of the area of the capital of the kabupaten, as well as by the implications of its location adjacent to a big city, the Municiality of Yogyakarta.